Penilaian Risiko Keamanan Bendungan Menggunakan Metode Andersen untuk Bendungan Haekrit: Risk Assessment Using Andersen Method on Haekrit Dam - Satrio, Irfan Rifqi (Universitas Islam 45, 2024)
Dam is a building across a river built with the aim of creating a reservoir. Due to the large volume of water, the dam has a very large potential for danger if failure occurs. Dams need to be managed properly, one of which is through regular inspections. The results of the inspection can be used to analyze dam risks. The Haekrit Dam was originally a reservoir whose classification was upgraded to dam due to the enactment of Minister of Public Works Regulation No. 27 of 2015 concerning Dams. The Haekrit Dam needs to be analyzed for its risks as a dam. The method for analyzing the risk of dams can use the modified Andersen method. This method works well for dams with limited information during construction and instrumentation. This research requires a report on the results of field inspections to determine the physical condition of the dam. The end result of this analysis is the dam risk condition in the form of a safety value (Naman). The safety value obtained is 78,1. Based on the risk assessment of the modified Andersen method, the Haekrit Dam has a safety value above 75 (satisfactory), which means that the dam is in good condition and has a low risk of failure. A satisfactory safety value means that the dam can operate properly at ordinary (normal) and extraordinary load times.